Macrophage-expressed CD51 promotes cancer stem cell properties via the TGF-β1/smad2/3 axis in pancreatic cancer. (10th September 2019) - Zhang, Bin; Ye, Huilin; Ren, Xiaofan; Zheng, Shangyou; Zhou, Quanbo; Chen, Changhao; Lin, Qing; Li, Guolin; Wei, Lusheng; Fu, Zhiqiang; Zhang, Yuting; Hu, Chonghui; et al.
Abstract: Macrophage-targeted therapy offers new options for intractable pancreatic ductal adenocarcinoma (PDAC), which has a low 5-year survival rate. However, the factors regulating the biological function and phenotype of macrophages in PDAC are incompletely understood. Here, we found that CD51 was positively associated with the poor prognosis of PDAC patients and was highly expressed on macrophages but not on pancreatic cancer cells. Subsequently, we found that CD51 was a marker of macrophages, which promoted the stemness of pancreatic cancer cells. Furthermore, knockdown of CD51 in macrophages drove macrophages toward an M1-like phenotype. Mechanistically, macrophage-expressed CD51 contributed to the acquisition of stemness traits of pancreatic cancer cells by regulating the TGF-β1/smad2/3 pathway. Our data demonstrate the central role played by macrophage-expressed CD51 in the acquisition of stemness traits of pancreatic cancer cells through the paracrine induction of TGF-β1. We first show the connection between the CD51/TGF-β1/smad2/3 axis and PDAC cancer stem cell properties and then indicate that CD51-targeted therapy is a new therapeutic modality for PDAC. Graphical abstract: Image 1 Highlights: CD51 is overexpressed in macrophages rather than cancer cells. CD51 promotes M2 type polarization of macrophages. CD51 increases the secretion of TGF-β1 in Macrophages. CD51/TGF-β1/smad2/3 axis promotes the stemness of pancreatic cancer cells.